2015
DOI: 10.1515/cclm-2015-0864
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of plasma vitamin K1 (phylloquinone) and K2 (menaquinones-4 and -7) using HPLC-tandem mass spectrometry

Abstract: The developed rapid and easy-to-use LC-MS/MS method for quantitative determination of PK, MK-4, and MK-7 in human plasma may be a good alternative for the labor-intensive and time-consuming LC-MS/MS methods and enables a higher sample throughput.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 28 publications
0
42
0
Order By: Relevance
“…In a study population of 60 renal transplant recipients, the authors confirmed that plasma PK concentrations were significantly associated with recent PK dietary intake and plasma MK-4 concentrations, and that plasma vitamin K levels were strongly correlated with plasma triglyceride concentrations [49].…”
Section: Determination Of Vitamin K Plasma Levels: Technical Aspectsmentioning
confidence: 71%
See 2 more Smart Citations
“…In a study population of 60 renal transplant recipients, the authors confirmed that plasma PK concentrations were significantly associated with recent PK dietary intake and plasma MK-4 concentrations, and that plasma vitamin K levels were strongly correlated with plasma triglyceride concentrations [49].…”
Section: Determination Of Vitamin K Plasma Levels: Technical Aspectsmentioning
confidence: 71%
“…Currently, an effective analytical method for assessing circulating vitamin K appears to be the one described by Riphagen et al [49], a liquid chromatography tandem mass spectrometry method for determination of three vitamers (PK, MK-4, and MK-7) with a simplified sample pre-purification process and reduced total run-time. Hopefully, this assay should avoid the interference by circulating triglycerides and should allow the identification of all vitamin K subtypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Riphagen et al published a LC‐MS method with APCI for determination of vitamins K 1 , MK‐4, and MK‐7 with a simplified pretreatment sample procedure. But the limit of quantification for MK‐7 was only 2.2 ng/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Low vitamin K concentrations are associated with increased risks of osteoporotic fractures in the elderly and vascular calcification . It was published that serum vitamin K concentrations are significantly associated with dietary intake of these vitamins . It is not entirely clear why there are no significant differences between populations but also between postmenopausal women in individual populations, and if only nutritional and metabolic factors play role.…”
Section: Discussionmentioning
confidence: 99%